(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
156 species of lichens and 44 species of lichenicolous fungi were found in the Trykraty granite massive. Lichenicolous fungi Cercidospora xanthoriae, Endococcus fusiger, Rosellinula frustulosae, Stigmidium squamariae, Tremella phaeophysciae, Xenonectriella leptaleae and lichen Coenogonium pineti are new for the steppe zone of Ukraine. 79 species of the lichens and 36 species of the lichenicolous fungi are reported for the first time for the National Nature Park “Buzky Gard”. Nine species were determined at the generic level and therefore require further identification. The exposed rock surfaces, seepage sites on granite, different soils in Aktovskiy, Arbuzynsky, Petropavlovsky canyons, ancient tree plantations in Nature Reserves “Labyrynt” and “Vasyleva Pasika” provided high gamma-diversity of the lichens and lichenicolous fungi in Trykraty granite massive. The nature habitats of this massive occupies of 750 ha and includes 200 species of lichens and lichenicolous fungi, therefore it is considered to be a hot-spot of biodiversity in plains of Ukraine. Eighty-four species of lichens were found in granite surfaces, 64 species – on bark of deciduous trees and only 12 species grow on soil between granite boulders. Thirty-six species of lichenicolous fungi were collected on saxicolous lichens. Lasallia pustulata is a lichen included in the Red Data Book of Ukraine which is protected in Trykraty department of the Natural Nature Park “Buzky Gard”. The lichens Acrocordia gemmata, Bacidia fraxinea, B. rubella, Caloplaca monacensis, Chaenotheca chlorella, C. trichialis, Cladonia uncialis, Coenogonium pineti, Lichinella nigritella, L. stipatula, Opegrapha niveoatra, Pseudoschismatomma rufescens, Ramalina intermedia, Scytinium gelatinosum, Xanthoparmelia loxodes and X. pokornyi were included to official list of species which require protection in Mykolaiv region.